Dairy trade liberalization and child stunting: Evidence from low- and middle-income countries - Liu, Xinghua; Liang, Yue; Chen, Kevin Z. (Elsevier, 2024)
Despite the well-studied nutritional benefits of dairy for child linear growth, dairy is less consumed in low- and middle-income countries (LMICs) where the prevalence of child stunting is high. Previous studies have suggested the cost of dairy as a potential barrier to increased dairy consumption in these countries. Surprisingly, little research on the association between dairy consumption and child stunting in LMICs focuses on the role of trade policies, particularly the liberalization of dairy trade. To explore this, we use representative cross-country individual data on child stunting from 2006 to 2020 and link it with country-level dairy trade data. We find that a 10% decline in dairy tariff rates reduces the risk of stunting by 7.78%. Our results are robust to a subsample analysis excluding countries which joined the WTO after 2000 and to an alternative clustering method. As a falsification test, our results show child stunting is not linked with tariffs for coffee and tea. Heterogeneity analysis indicates the associations are more pronounced for boys, children aged 3–5, and children from households with lower socioeconomic status. Although we did not find significant rural–urban differences, the associations are indeed stronger for households without cattle and for countries in Western Africa, South East Asia and Europe and Central Asia. Mechanism analysis suggests that dairy tariffs are positively correlated with milk prices, while they are negatively associated with dairy import values. Lower dairy tariffs are also found to be linked with higher probability of child dairy consumption. Our findings highlight the importance of removing tariff barriers in reducing the cost of dairy and promoting dairy consumption in LMICs. This study has implications for repurposing dairy trade policies in creating nutrition-sensitive agriculture.